Lecture summaries - Macinnes, Lesley; Keppie, L J F; Millett, M; Jackson, Anthony; Burnett, Charles J; Pursiuvant, Dingwall (Proceedings of the Society of Antiquaries of Scotland, 1987)
Five lecture summaries: Roman and native in south-east Scotland: the problem and the potential Monumenta Romani Imperil, recent work on Roman inscriptions and sculptured reliefs from Scotland Town and country in Roman Britain: a social perspective Pictish symbols: their meaning and usage Funeral heraldry in Scotland